Utilization of Andong Leaf Extract (Cordyline fruticosa) as an Alternative for Coloring the Eggs of Intestinal Nematode - Supriyanto; Linda Triana (POLTEKKES KEMENKES PONTIANAK, 2021)
Microscopic examination is essential to find the type of worm that causes infection. Direct examination of worm eggs needs to use staining to distinguish between worm eggs and food residues that are not completely digested. The dyes commonly used are synthetic. The purpose of this study was to replace synthetic dyes with natural dyes with Andong (Cordyline Fruticosa) leaf juice. It can be used as an alternative or a substitute for dyes. This research method is descriptive, conducted at the Parasitology Laboratory of Poltekkes Kemenkes Pontianak. The population in this study was the juice of the leaves of Andong (Cordyline Fruticosa). The method of inspection is direct preparation with an object glass as is routinely done, but the dye is replaced with Andong leaf juice (Cordyline Fruticosa). The results showed that natural dye Andong leaf juice (Cordyline Fruticosa), gave a clear color to the absorption of intestinal nematode worm eggs as the test target. This study concludes that the juice of the leaves of Andong (Cordyline Fruticosa) with alcohol solvent can be used as an alternative dye for the examination of intestinal nematode worm eggs.